The effects of education program introducing Italy as a country and culture to 5-6 year-old children - (:unkn) unknown (ELSEVIER SCIENCE BV, 2009)
In this study effectiveness of an intercultural education program that describing Italy with its various qualities as a country and culture was tested with an experimental study. The study is based on data from test and control groups. 5-6 year-old children attending the same pre-school are randomly assigned to test and control groups of 15 children. The test group is specifically presented with the program while the same subject (Italy) is presented to the control group with a more conventional approach. Information of the children in both test and control groups about the country in question is measured with a survey. The forms of survey were filled out by teachers and preliminary and post test examination. At the preliminary and post test evaluation the children are also presented face-to-face with a list of illustrated questions that are prepared in computer. The data are evaluated with appropriate statistical analysis methods. As a result of investigating effectiveness of the Program Describing Italy as a Country and Culture applied on children in test group, results according to self-evaluation of both teachers and children indicate a meaningful difference in the favour of test group. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: 5-6 year-old children; intercultural learning; Italy